The Impact of Mud Shale on Water and Nutrient Transport in Soil - Zhang, Panpan; Zhang, Jing; Gao, Shu (Scientific Journal of Technology, 2025)
Mud shale, a fine-grained sedimentary rock rich in clay minerals and organic matter, has been identified as a potential material for improving soil structure and enhancing water and nutrient retention. This study investigates the impact of mud shale on water and nutrient transport in soil, focusing on its physical and chemical properties and their implications for soil health and plant growth. Through a combination of laboratory experiments and field studies, this research explores how the addition of mud shale can modify soil porosity, permeability, and nutrient availability, ultimately affecting water and nutrient transport dynamics. The findings suggest that mud shale can significantly enhance soil structure and improve water retention and nutrient cycling, offering a sustainable solution for soil improvement and ecological restoration.